Effect of cross-linking agents on the adsorption of histamine on molecularly imprinted polyacrylamide. (22nd February 2023) - Boukadida, Merymene; Jaoued-Grayaa, Najeh; Anene, Amira; Chevalier, Yves; Hbaieb, Souhaira
Abstract: The ability of molecularly imprinted polymers (MIPs) prepared with flexible cross-linking agents for selective uptake of guest molecules is investigated. New polyacrylamide polymers had been synthesized for histamine (HA) extraction using solid supports based on MIPs immobilized on silica surface (SiO2 ). The MIPs were prepared via radical polymerization in acetonitrile and in the presence of azobisisobutyronitrile (AIBN) as initiator, using HA as a target molecule, acrylamide as a functional monomer and several cross-linking agents having alkyl spacers of various lengths: N, N ′-methylenebisacrylamide (BA1 ), N, N ′-ethylenebisacrylamide (BA2 ), N, N '-(butane-1, 4-diyl)-bis(2-methacrylamide) (BA4 ) and N, N '-(hexane-1, 6-diyl)-bis(2-methacrylamide) (BA6 ). All the prepared MIPs have a strong absorption capacity of HA compared to non-imprinted polyacrylamide (NIPs). MIP4 made with the BA4 cross-linker shows a higher selectivity for adsorption of HA than MIPs made with BA1, BA2 and BA6 . Thus, the imprinting factor for adsorption from a 5 ppm HA solution was 2.5 for MIP4 against 1.4 to 1.6 for MIP1, MIP2 and MIP6 . Langmuir–Volmer and Volmer models of the adsorption isotherms of MIPs and NIPs accurately fit the experimental data. They provide the characteristic parameters of the adsorption thermodynamic of the materials. The higher performance of MIP4 for selective adsorption of HA is mainly coming from a higher density of molecular imprints (1.4 μmol m −2 against 0.13–0.15 μmol m −2 for MIP1 and MIP2 and 0.4 μmol m −2 for MIP6 ) than a higher affinity of HA for the molecular imprints. The selectivity with respect to the tyramine and melamine interfering molecules is also higher for MIP4 . As the main outcome, some moderate flexibility of the material is advantageous. Such flexibility allows for a reversible healing and re-opening of the molecular imprints as the HA guest is removed and back-adsorbed. Graphical abstract: Image 1 Highlights: Flexible spacer of cross-linking agent improves the performance of MIPs. MIP as thin layers of cross-linked polyacrylamide selectively binds histamine. Selective and non-selective adsorption from modeling adsorption thermodynamics.